Analysis of Aneuploidy Rate and Pregnancy Outcomes in Unexplained Recurrent Pregnancy Loss Couples With Chromosome Polymorphism After PGT-A - Cao, Mingzhu; Zhang, Qian; Zhou, Wei; Zhu, Yueting; Li, Hongchang; Yan, Junhao (Frontiers in Medicine, 2022)
Purpose The study aims to investigate whether chromosomal polymorphism affects embryo development and pregnancy outcomes of unexplained recurrent pregnancy loss (uRPL) couples undergoing PGT-A. Methods A total of 585 couples with uRPL history who performed PGT-A were included in the retrospective study from January 2016 to December 2020. We included 415 couples with normal karyotype and 170 couples with chromosomal polymorphism. Furthermore, the polymorphism group was divided into two subgroups: 113 couples in the male group and 57 couples in the female group. The embryo development and pregnancy outcomes were analyzed in different groups. Results The blastocyst rate and aneuploidy rate are statistically different in the normal group, male polymorphism group, and female polymorphism group. Compared with normal and female groups, the male group has a lower blastocyst rate, which is statistically different (48.3 vs. 53.9%, p = 0.003; 48.3 vs. 54.1%, p = 0.043). Moreover, the aneuploidy rate of the male polymorphism group is significantly higher than female carriers (29.5 vs. 18.6%, p = 0.003). However, there were no statistically significant differences in clinical pregnancy rate, early miscarriage rate, and live birth rate after PGT-A (p > 0.05). Conclusion Male with chromosome polymorphism (CPM) have a lower blastocyst rate and a higher aneuploidy rate than female carriers in uRPL couples undergoing PGT-A. However, when a euploid blastocyst was first transferred, no difference in pregnancy outcomes was found between the male and female polymorphism carriers. It indicated that CPM may have an adverse effect on the embryos of male carriers with uRPL history, and the occurrence of uRPL may be decreased in male polymorphism carriers after PGT-A.